Strategic management world edition (3G E-Learning LLC, 2023)
"This edition is completely revised and new topics are added. This comprehensive text entitled Strategic Management is a balanced coverage of both theory and practice, dealing with the essential elements of strategy making and concentrates on how the environmental context can be read to identify opportunities which will create and maintain competitive advantage." -- Preface